Examination the effectiveness of self-compassion intervention to reduce body dissatisfaction among Malaysian young adults - Yusri, Nurain Md (2022)
With the rise of mental health issues among adults, the exploration of psychological interventions can be diversified to cater to this need as a public health measure of improving general wellbeing. One issue of concern is body dissatisfaction which influences individuals’ perception of their own physical appearance negatively. Research shows high levels of self-compassion is positively linked to better aspects of mental health and has benefits for body dissatisfaction. Previous studies found benefits of self-compassion intervention in reducing psychopathology including symptoms of body dissatisfaction. The current study aimed to examine whether there is a benefit of selfcompassion intervention techniques in reducing levels of body dissatisfaction among young adults. To examine this, pre-and post-experimental design was conducted to see whether online self-compassion intervention has benefits on two aspects which are self-compassion and body dissatisfaction. Nine undergraduate students fully completed the brief online self-compassion group intervention. They participated in a bi-weekly 1-hour online group intervention for four weeks, for eight sessions. Self- Compassion Scale (SCS) and Body Shape Questionnaire (BSQ) were used to measure their levels of self-compassion and body dissatisfaction respectively. The participant’s pre- and post-intervention level of self-compassion and body dissatisfaction were compared to identify any significant differences. Paired t-test statistical analysis showed no difference in both self-compassion level and body dissatisfaction level before and after the intervention. The current study lacks sample size to arrive at a conclusive result. However, the intervention did not negatively affect levels of self-compassion or body dissatisfaction and can be considered safe. Implications are discussed and recommendation for future research is included.